An electrochemical sensor based on heteroatom doped carbon material and a preparation method thereof
Patent Information
- Application Number
- CN202611142275.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-30
AI Technical Summary
但常规水凝胶与有机聚合物本征导电性较差,会增大电极的整体电阻,削弱电子传导效率;且普通水凝胶的多孔结构多为无序分布,孔道连通性差、孔径分布不均,待测分子在电极内部的扩散路径曲折,传质效率提升效果有限
1.本发明的杂原子掺碳材料形成的带正电的活性位点能够静电吸附,主动富集新烟碱类分子的靶标分子,同时这些活性位点能够提供高密度活性位点,放大电流响应,另一方面,三维的气凝胶小尺寸孔道能够提升活性位点利用率,从而能够检测到极低浓度的农药残留,将呋虫胺检出限低至0.22μM,线性范围覆盖0.1~50μM。
Smart Images

Figure CN122671518B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical sensor technology, and more specifically, to an electrochemical sensor based on heteroatom-doped carbon materials and its preparation method. Background Technology
[0002] Neonicotinoid pesticides are widely used in global agricultural production to control piercing-sucking pests due to their broad-spectrum insecticidal activity and good systemic properties. Residue control in fruits, vegetables, grains, and other agricultural products is a crucial aspect of agricultural product quality and safety supervision. Currently, the mainstream techniques for quantitative pesticide residue detection are high-performance liquid chromatography (HPLC) and liquid chromatography-tandem mass spectrometry (LC-MS / MS). While these methods offer high precision and accurate quantification, they rely on large, sophisticated instruments, require professional personnel for operation, involve cumbersome sample pretreatment steps, and have long testing cycles. These methods cannot meet the needs of rapid on-site screening in fields, farmers' markets, and grassroots regulatory stations, and are ill-suited for large-scale, high-throughput daily monitoring scenarios.
[0003] Electrochemical sensing technology, with its advantages of miniaturized instruments, low detection costs, fast response speed, and on-site operation, has become a key research direction in the field of rapid pesticide residue detection. The performance of electrode modification materials is the core factor determining the detection sensitivity, detection limit, and stability of electrochemical sensors. Carbon-based materials, due to their excellent electronic conductivity, large theoretical specific surface area, and good chemical stability, are widely used as active materials for modifying electrochemical sensing electrodes. Common types include activated carbon, carbon nanotubes, graphene, and biomass-derived char.
[0004] However, in actual preparation and application, due to their high surface energy, nanoscale carbon material particles are prone to spontaneous aggregation and stacking due to strong van der Waals forces between them. This results in a large number of active sites that were originally inside the particles being encapsulated, preventing them from fully contacting the electrolyte to be tested, and significantly reducing the effective electroactive area of the electrode. At the same time, the dense stacked structure formed by aggregation will block the diffusion channels of the electrolyte, increase the mass transfer resistance inside the electrode, and cause obvious concentration polarization, ultimately limiting the improvement of sensor detection sensitivity and response speed.
[0005] To improve the electrochemical performance of carbon-based materials, heteroatom doping is a commonly used modification method. By introducing heteroatoms into the carbon framework, the electronic structure of carbon materials is modulated, increasing surface defect sites to enhance electrocatalytic activity. Existing publicly available technologies mostly use elements such as nitrogen and oxygen for doping modification, which has limited effect on improving the catalytic activity of carbon materials. Furthermore, doping modification can only optimize the catalytic properties of the carbon material itself and cannot fundamentally solve the problem of carbon particle aggregation. The actual utilization rate of active sites is still limited by the aggregation effect.
[0006] To alleviate the problem of carbon material agglomeration, some existing technologies use hydrogels and organic polymers as support frameworks to disperse carbon materials in a polymer matrix to prepare composite electrodes. However, conventional hydrogels and organic polymers have poor intrinsic conductivity, which increases the overall resistance of the electrode and weakens the electron conduction efficiency. Moreover, the porous structure of ordinary hydrogels is mostly disordered, with poor pore connectivity and uneven pore size distribution, resulting in tortuous diffusion paths for analyte molecules within the electrode and limited improvement in mass transfer efficiency. At the same time, the bonding between ordinary polymer frameworks and carbon materials is only physical, with weak adhesion. During repeated use of the electrode, the active material is prone to detachment, leading to rapid degradation of detection performance and making it difficult to guarantee the repeatability and long-term stability of the electrode. Summary of the Invention
[0007] To overcome the shortcomings of existing electrochemical sensors, this invention provides an electrochemical sensor based on heteroatom-doped carbon materials and its preparation method.
[0008] The technical solution of this invention is as follows: An electrochemical sensor based on heteroatom-doped carbon material is used to detect neonicotinoid pesticides. The sensor includes a working electrode, a counter electrode, and a reference electrode. The working electrode includes a porous support substrate and a functional surface layer. The functional surface layer is a continuous porous solid layer that covers and is embedded in the surface pores of the porous support substrate. The functional surface layer is a composite material of heteroatom-doped carbon material and nanocellulose aerogel. The nanocellulose in the nanocellulose aerogel interweaves to form a continuous skeleton structure. After the heteroatom-doped carbon material and nanocellulose hydrogel are mixed, they are subjected to directional freezing and freeze-drying treatment to induce the directional growth of ice crystals, so that the nanocellulose hydrogel forms directionally arranged, interconnected channels, thus forming a composite material of heteroatom-doped carbon material and nanocellulose aerogel. Heteroatom-doped carbon materials are materials formed by mixing carbon precursors and heteroatom dopants and then heat-treating them at high temperatures. The carbon precursors have a porous structure, and the heteroatom dopants are embedded in the carbon lattice of the carbon precursors after heat treatment at high temperatures, forming a heteroatom-carbon doped structure and active sites.
[0009] The aforementioned electrochemical sensor based on heteroatom-doped carbon materials includes a doped structure formed by the heteroatom dopant and the carbon precursor after high-temperature heat treatment. (1) Substitutional doping structure, where heteroatoms replace carbon atoms in the carbon precursor; (2) Defect-type doped structure: after heteroatoms are embedded in carbon precursors, carbon lattice is distorted, edge defects or structural vacancies are formed, thus forming active defect sites.
[0010] The aforementioned electrochemical sensor based on heteroatom-doped carbon materials has oxygen-containing functional groups on its surface, and the hydroxyl groups on the surface of nanocellulose form hydrogen bonds with the oxygen-containing functional groups on the surface of the heteroatom-doped carbon materials.
[0011] The aforementioned electrochemical sensor based on heteroatom-doped carbon materials uses at least one of the following as the carbon precursor: hydrothermal biochar, activated carbon, carbon nanotubes, graphene, graphene oxide, and biomass carbon sources.
[0012] The aforementioned electrochemical sensor based on heteroatom-doped carbon materials uses heteroatom dopants that are any one or more boron-containing compounds, sulfur-containing compounds, or phosphorus-containing compounds.
[0013] Specifically, the boron-containing compound is any one or more of boron oxide, boric acid, or borax; the sulfur-containing compound is any one or more of thiourea, sulfur powder, sulfate, or thiophene; and the phosphorus-containing compound is any one or more of phosphoric acid, phosphate, or phytic acid.
[0014] The aforementioned electrochemical sensor based on heteroatom-doped carbon materials uses porous filter cotton as its porous support substrate.
[0015] A method for fabricating an electrochemical sensor based on heteroatom-doped carbon materials, wherein the method for fabricating the working electrode of the sensor includes... Step S1. Mix the carbon precursor with the heteroatom dopant and perform high-energy ball milling. Then, perform high-temperature heat treatment and purification treatment in an inert gas environment to obtain the heteroatom-doped carbon material. Step S2. Mix and homogenize the heteroatom-doped carbon material obtained in step S1 with nanocellulose hydrogel to obtain a composite sol; Step S3. Load the composite sol from step S2 onto a porous substrate and perform directional freeze-drying to obtain a composite electrode of heteroatom-doped carbon material and nanocellulose aerogel, thus obtaining the working electrode of the sensor.
[0016] The above-mentioned method for preparing an electrochemical sensor based on heteroatom-doped carbon materials involves using stainless steel grinding balls in a high-energy ball mill, with a ball-to-material ratio of 10:1 to 100:1, a rotation speed of 100 to 1000 rpm, and a time of 0.5 to 10 hours.
[0017] The above-mentioned method for preparing an electrochemical sensor based on heteroatom-doped carbon materials includes a directional freezing and freeze-drying process comprising: placing a composite sol of heteroatom-doped carbon materials and nanocellulose hydrogel at -50 to -80°C for 10 to 30 minutes, and then freeze-drying it at a pressure of 0.005 to 0.05 mbar for 48 to 96 hours.
[0018] The above-mentioned method for fabricating an electrochemical sensor based on heteroatom-doped carbon materials includes the following high-temperature heat treatment conditions after mixing the carbon precursor with the heteroatom dopant: (1) Inert gas environment; (2) The heating rate is 5–20 °C / min; (3) The heat preservation temperature is 500-1500℃, and the heat preservation time is 1-5 hours; After high-temperature heat treatment, it is naturally cooled and then purified.
[0019] In the above-mentioned method for preparing an electrochemical sensor based on heteroatom-doped carbon materials, the mass ratio of carbon precursor to heteroatom dopant in the heteroatom-doped carbon materials is 10:1 to 1:5.
[0020] The above-mentioned method for preparing an electrochemical sensor based on heteroatom-doped carbon material involves a ratio between the heteroatom-doped carbon material and the nanocellulose hydrogel as follows: 0.01 to 0.5 g of heteroatom-doped carbon material is added to every 10 mL of nanocellulose hydrogel, and the mass fraction of the nanocellulose hydrogel is 0.5 to 5 wt%.
[0021] The working electrode comprises a porous support substrate and a functional surface layer loaded on the porous support substrate, namely a composite material of heteroatom-doped carbon material and nanocellulose aerogel. The heteroatom-doped carbon material provides a high density of electrocatalytic active sites and excellent electron conductivity, while the nanocellulose aerogel constructs efficient mass transport channels and a large reaction interface.
[0022] The composite material of heteroatom-doped carbon materials and nanocellulose aerogel is a three-dimensional porous network structure formed by mixing heteroatom-doped carbon materials and nanocellulose hydrogels, followed by directional freeze-drying. In this process, numerous hydroxyl (-OH) groups on the surface of nanocellulose form hydrogen bonds with oxygen-containing functional groups on the surface of the heteroatom-doped carbon materials, achieving a tight and stable bond at the molecular scale. This inhibits the aggregation of the nanocarbon materials and ensures their uniform dispersion. Furthermore, by employing directional freeze-drying technology to control the growth of ice crystals in one direction (e.g., vertically), the hydrogel structure forms an aerogel after freeze-drying. This aerogel contains interconnected micron-sized channels arranged in a specific direction. This directional porous structure provides high-speed diffusion channels for electrolyte ions and target molecules, shortening the mass transfer path and reducing concentration polarization.
[0023] Heteroatom-doped carbon materials are hybrid materials prepared by high-energy ball milling of carbon precursors and heteroatom dopants followed by high-temperature heat treatment. The heteroatoms in these materials are at least one of boron, sulfur, and phosphorus. Boron atoms have a similar atomic radius to carbon but are electron-deficient. When boron atoms replace carbon atoms in the carbon lattice, they disrupt the charge balance of the carbon skeleton, forming positively charged active sites. These sites exhibit strong electrostatic adsorption on electron-rich neonicotinoid pesticide molecules, effectively enriching the target molecules. Simultaneously, boron doping induces more edge and structural defects in the carbon material. These defect regions are highly active centers for electrocatalytic reactions, reducing the overpotential and thus increasing the redox reaction rate. Phosphorus and sulfur atoms are larger than carbon atoms. When these two atoms are doped with carbon materials, they cause local distortion and expansion of the carbon lattice, generating significant strain effects and structural defects. This alters the local electronic structure of carbon atoms, giving them superior adsorption energy for reaction intermediates and enhancing their catalytic activity against pesticide molecules. In addition, the introduction of oxygen-containing functional groups (CO, PO, SO, BO) in heteroatom-doped carbon materials improves the wettability of the electrode in aqueous electrolytes and promotes the accessibility of active sites.
[0024] The molecular skeleton of neonicotinoid pesticide molecules contains pyridine / thiazole heterocycles and also contains strong electron-donating groups such as nitro and imino groups, exhibiting overall electron-rich characteristics. The heteroatom-doped carbon material of this invention introduces heteroatoms (boron, phosphorus, sulfur) into the carbon lattice. The introduction of heteroatoms causes lattice defects and edge defects in the carbon lattice, forming positively charged active sites that generate strong electrostatic attraction with electron-rich neonicotinoid molecules, actively enriching target molecules on the electrode surface. The nitro and heterocyclic structures of neonicotinoid pesticides have clear redox potential windows at these carbon defect sites. The doping of heteroatoms (boron, sulfur, phosphorus) regulates the electron cloud distribution of the carbon material, optimizing the adsorption energy of reaction intermediates for this type of pesticide, reducing the reaction overpotential, allowing target molecules to react at lower voltages, and simultaneously amplifying the electrostatic potential. On the one hand, common interfering substances such as sucrose, glucose, and inorganic salts do not undergo significant electrochemical reactions at the same potential, thus they do not generate interference signals. In addition, the nanocellulose aerogel on the working electrode has interconnected channels formed by directional freezing and freeze-drying, with channel sizes reaching the micrometer level. Therefore, these interconnected channels can accommodate the diffusion of neonicotinoid small molecule pesticides. Meanwhile, large molecules (proteins, polysaccharides, pigments, etc.) commonly found in agricultural product matrices are difficult to enter the pores to contact active sites due to their large size, thus achieving a size sieving effect, improving the selectivity for detecting small molecule pesticides and reducing matrix interference.
[0025] According to the above-described solution, the beneficial effects of this invention are as follows: 1. The positively charged active sites formed by the heteroatom-doped carbon material of the present invention can electrostatically adsorb and actively enrich target molecules of neonicotinoids. At the same time, these active sites can provide high-density active sites and amplify the current response. On the other hand, the three-dimensional aerogel with small-sized pores can improve the utilization rate of active sites, thereby enabling the detection of extremely low concentrations of pesticide residues, reducing the detection limit of fipronil to 0.22 μM, and covering a linear range of 0.1–50 μM.
[0026] 2. The working electrode of this invention exhibits molecular selectivity in electrostatic adsorption, enriching only electron-rich targets such as neonicotinoid molecules. Furthermore, the size of the aerogel channels can act as a sieve, blocking large molecular interferences. Therefore, when 500 μM sucrose, glucose, and 2500 μM inorganic ions coexist, the current change rate of this invention is <3%, avoiding interference from agricultural products and other substances.
[0027] 3. The electrochemical workstation used in the working electrode of this invention is small in size and portable. The sample pretreatment steps are simple, requiring no complex purification or treatment. The single detection time is short, which is beneficial for rapid screening scenarios such as fields, supermarkets, and farmers' markets.
[0028] 4. In the working electrode of this invention, carbon particles are supported on the surface of nanocellulose or on the inner walls of the network pores. The carbon particles are physically separated by nanocellulose, losing the spatial conditions for close proximity and tight stacking, thus inhibiting carbon agglomeration. Directional freeze-drying not only fixes the relative positions of cellulose and carbon particles during the process, but also allows ice crystals to sublimate directly during drying, eliminating the strong capillary forces of conventional liquid-phase evaporation and preventing carbon particles from being squeezed and agglomerated during drying. Furthermore, the formed through-holes shorten the mass transfer path and reduce concentration polarization. Additionally, heteroatom doping introduces a large number of defective active sites. The boron-doped electrode has an electroactive area of 0.209 cm², almost the same as the undoped electrode (0.112 cm²). 2 It is nearly twice that of ).
[0029] 5. The cellulose hydroxyl groups of the present invention form hydrogen bonds with carbon materials, and the molecular-level binding prevents the active material from falling off. The directional freeze-drying process is controllable, the batch consistency is high, the RSD of 10 repeated tests on the same electrode is 2.78%, the reproducibility RSD of 5 independent electrodes is 3.90%, and 85.98% of the response is retained after 14 days of storage at 4°C. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a scanning electron microscope image of the undoped carbon material obtained in Example 1.
[0032] Figure 2 This is a scanning electron microscope image of the boron-doped carbon material obtained in Example 2.
[0033] Figure 3 This is a scanning electron microscope image of the composite material of undoped carbon material and nanocellulose aerogel obtained in Example 3.
[0034] Figure 4 This is a scanning electron microscope image of the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4.
[0035] Figure 5 The X-ray diffraction patterns of the composite materials obtained in Examples 3 and 4 are shown.
[0036] Figure 6 The images show the Raman spectra of the composite materials obtained in Examples 3 and 4.
[0037] Figure 7 The images show the N2 adsorption-desorption isotherms of the composite materials obtained in Examples 3 and 4, respectively.
[0038] Figure 8 The graphs show the pore size distribution curves of the composite materials obtained in Examples 3 and 4.
[0039] Figure 9 Cyclic voltammetry curves of composite materials of undoped carbon materials and nanocellulose aerogels at different scan rates.
[0040] Figure 10 Cyclic voltammetry curves of composite materials of heteroatom-doped carbon materials and nanocellulose aerogels at different scan rates.
[0041] Figure 11 Linear fitting curves of peak current versus square root of scan rate for composite materials of undoped carbon materials and nanocellulose aerogels and composite materials of heteroatom-doped carbon materials and nanocellulose aerogels at different electrodes.
[0042] Figure 12 The response curves of a sensor formed by a composite material of heteroatom-doped carbon material and nanocellulose aerogel to different concentrations of fipronil.
[0043] Figure 13 The peak current of the sensor formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel is a bilinear fit plot with the concentration of fipronil.
[0044] Figure 14 The graph shows the repeatability test results of the working electrode formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4.
[0045] Figure 15 The graph shows the reproducibility test results of the working electrode formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4.
[0046] Figure 16 The figure shows the stability test results of the working electrode formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4. Detailed Implementation
[0047] To make the technical problems to be solved, the technical solutions, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Example 1
[0048] Take 10g of hydrothermal biochar (HTC) and coarsely grind it at 30rpm for 30min using a vibratory disc mill. Place the coarsely ground HTC in a planetary high-energy ball mill with a ball-to-material ratio of 50:1 and ball mill at 450rpm for 2 hours. Place the ball-milled powder in a tube furnace and heat it to 700℃ at 10℃ / min under argon atmosphere, hold it at that temperature for 2 hours, and then allow it to cool naturally. Wash the cooled product three times each with 80℃ hot water, 1mol / L dilute hydrochloric acid, ultrapure water, and anhydrous ethanol, and then vacuum dry to obtain undoped carbon material.
[0049] The scanning electron microscope image of the undoped carbon material obtained in Example 1 is shown below. Figure 1 As shown. Example 2
[0050] Take 10g of hydrothermal biochar (HTC) and coarsely grind it at 30rpm for 30min using a vibratory grinder. Mix the coarsely ground HTC with boron oxide (B2O3) at a mass ratio of 3:1 and place it in a planetary high-energy ball mill with a ball-to-material ratio of 50:1. Ball mill at 450rpm for 2 hours. Place the ball-milled powder in a tube furnace and heat it to 700℃ at 10℃ / min under argon atmosphere, hold it at that temperature for 2 hours, and then allow it to cool naturally. Wash the cooled product three times each with 80℃ hot water, 1mol / L dilute hydrochloric acid, ultrapure water, and anhydrous ethanol, and then vacuum dry to obtain boron-doped carbon material.
[0051] Scanning electron microscope image of the boron-doped carbon material obtained in Example 2 is shown below. Figure 2 As shown. Example 3
[0052] 0.1g of the undoped carbon material from Example 1 was added to 10g of 1.0wt% nanocellulose hydrogel, and stirred at 2000rpm for 10 minutes using a high-speed homogenizer to obtain a homogeneous composite sol. A porous support substrate (porous filter cotton) was cut to a size suitable for the working electrode and placed in a plastic petri dish as a carrier substrate. The composite sol was uniformly loaded onto the surface of the filter cotton and allowed to stand for 30 minutes to eliminate air bubbles. Liquid nitrogen was added under a copper plate, and the petri dish was placed on the copper plate and directionally frozen for 20 minutes. After complete freezing, it was transferred to a freeze dryer and freeze-dried at -70℃ and 0.01mbar for 72 hours to obtain a composite material of undoped carbon material and nanocellulose aerogel.
[0053] The scanning electron microscope image of the composite material of undoped carbon material and nanocellulose aerogel obtained in Example 3 is shown below. Figure 3 As shown. Example 4
[0054] 0.1g of the boron-doped carbon material from Example 2 was added to 10g of 1.0wt% nanocellulose hydrogel, and stirred at 2000rpm for 10 minutes using a high-speed homogenizer to obtain a homogeneous composite sol. A porous support substrate (porous filter cotton) was cut to a suitable size for the working electrode and placed in a plastic petri dish as a carrier substrate. The composite sol was uniformly loaded onto the surface of the filter cotton and allowed to stand for 30 minutes to eliminate air bubbles. Liquid nitrogen was added under a copper plate, and the petri dish was placed on the copper plate and directionally frozen for 20 minutes. After complete freezing, it was transferred to a freeze dryer and freeze-dried at -70℃ and 0.01mbar for 72 hours to obtain a composite material of heteroatom-doped carbon material and nanocellulose aerogel, i.e., the composite electrode (working electrode).
[0055] The scanning electron microscope image of the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4 is shown below. Figure 4 As shown, from Figure 4 As can be seen, carbon particles are uniformly loaded on the three-dimensional network framework of nanocellulose aerogel with vertically oriented pores.
[0056] like Figure 5 , Figure 6 As shown, after carbon materials are doped with heteroatoms, the impurity peaks disappear and the orderliness of the carbon structure is improved.
[0057] like Figure 7 , Figure 8 , Figure 9 As shown, compared with undoped carbon materials, boron-doped carbon materials have a higher specific surface area and mesopore volume.
[0058] The electrochemical sensor of this invention employs a three-electrode system. The working electrode is the composite electrode prepared in Example 4, the counter electrode is a platinum sheet, and the reference electrode is a saturated calomel electrode. The electrochemical sensor composed of these three electrodes was tested on a portable electrochemical workstation. The process of determining the test conditions included: (1) Optimization of incubation time: Incubation, also known as the enrichment process, was tested in a portable electrochemical workstation. The DPV response was measured at different incubation times (1–25 minutes) in 0.1M PBS (pH 7.0) containing 50 μM fipronil. That is, all other conditions, such as fipronil concentration of 50 μM and buffer pH 7.0, were kept constant, and only the incubation time was changed (1–25 minutes, changed minute by minute), and the peak current of differential pulse voltammetry was measured. The results showed that the peak current increased with the extension of incubation time and tended to reach equilibrium after 15 minutes. 15 minutes was selected as the optimal incubation time.
[0059] (2) pH optimization: The working electrode was tested in a portable electrochemical workstation within a pH range of 6.0 to 8.0. That is, the pesticide concentration, incubation time, scan rate and other conditions were kept constant, and only the pH of the PBS buffer was changed (6.0 to 8.0), and the change in peak current was tested. The results showed that the peak current was the largest when pH=7.0, and the pH of the buffer was selected as 7.0.
[0060] (3) Effect of scan rate: The working electrode was tested in a portable electrochemical workstation, i.e., with other conditions fixed, multiple scan rates were set in the range of 10–200 mV / s to test the peak current of the cyclic voltammetry curve, and then linear fitting was performed. The results showed that in the range of 10–200 mV / s, the peak current was related to ν. 1 / 2 The linear relationship indicates that the reaction is diffusion-controlled, and the selected scan rate is 50 mV / s.
[0061] Performance test of working electrode 1: Performance testing included the application of cyclic voltammetry to detect and calculate the theoretical electroactive area of the working electrode. Cyclic voltammetry was used at different scan rates (10 mV / s, 20 mV / s, 30 mV / s, 40 mV / s, 60 mV / s, 80 mV / s, 100 mV / s, 120 mV / s, 140 mV / s, 160 mV / s, and 200 mV / s) to detect the cyclic voltammetric curves of the undoped carbon material and nanocellulose aerogel composite obtained in Example 3 and the heteroatom-doped carbon material and nanocellulose aerogel composite obtained in Example 4. The cyclic voltammetric curves of these two materials are shown below. Figure 9 , Figure 10 , Figure 11 The theoretical electroactive area of the composite material of undoped carbon material and nanocellulose aerogel obtained in Example 3 was calculated to be 0.112 cm². 2The theoretical electroactive area of the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4 is 0.209 cm². 2 .
[0062] Performance test of working electrode 2: Performance testing included the detection of different concentrations of fipronil (0.1–50 μM) using a differential pulse voltammetry working electrode. Under the optimized incubation time (15 minutes), optimized pH (7.0), and optimized scan rate (50 mV / s) conditions described above, the working electrode formed from the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4 was used to detect different concentrations of fipronil buffer solution. The detection results are as follows: Figure 12 , Figure 13 As shown, the peak current and the concentration of fipronil showed a bilinear relationship in the ranges of 0.1–2 μM and 2–50 μM. The linear regression equation for the low concentration range was I(μA) = 8.508 + 3.614C (R² = 0.9738), and the detection limit was 0.22 μM (S / N = 3).
[0063] Performance test of working electrode 3: Performance testing included adding interfering substances (500 μM sucrose, 500 μM glucose, 2500 μM sodium ions, 2500 μM potassium ions, and 2500 μM ammonium ions) to a 50 μM buffer solution containing fipronil, to detect the response of the working electrode formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4 to fipronil. The peak current change rates of the working electrode formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel to sucrose, glucose, sodium ions, potassium ions, and ammonium ions were measured to be 0.80%, 2.74%, 0.59%, 0.20%, and 1.52%, respectively, indicating that the working electrode formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel has good anti-interference ability against macromolecules and inorganic ions.
[0064] Performance test of working electrode, part four: Performance testing included multiple tests with the same fipronil buffer to determine the repeatability of the working electrode. A working electrode formed from the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4 was tested 10 times consecutively with 50 μM fipronil buffer. The results are as follows: Figure 14 As shown, the coefficient of variation (RSD) of the working electrode is 2.78%.
[0065] Performance test of working electrode, part five: Performance testing included simultaneously testing multiple working electrodes made of the same material with fipronil buffer to determine the reproducibility of the working electrodes. Five working electrodes were prepared using composite materials of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4, and simultaneously tested with fipronil buffer containing the same concentration (50 μM). The test results are as follows: Figure 15 As shown, the coefficient of variation (RSD) for different working electrodes is 3.90%.
[0066] Performance test of working electrode, part six: Performance testing included storing the working electrode at a specific temperature for several days and then testing it against fipronil buffer to determine its stability. A working electrode was prepared using a composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4. The working electrode was stored at 4°C for 1, 4, 7, 10, and 14 days, and then tested against fipronil buffer. The results are as follows: Figure 16 As shown, the working electrode formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel retains 85.98% of its initial peak current response after being stored at 4°C for 14 days.
[0067] Spiked recovery experiments were conducted using brown rice as a sample to test the actual performance of the sensor formed by the composite material of heteroatom-doped carbon material and nanocellulose aerogel obtained in Example 4. 10g of pulverized and mixed brown rice was extracted with 20mL of acetonitrile and centrifuged at 5000r / min. 10mL of the supernatant was rotary evaporated to near dryness and reconstituted with 0.1M PBS (phosphate buffer) (pH=7.0). The solution was divided into three equal portions, and 1.0μM, 10.0μM, and 25.0μM dinotefuran standards were added to each portion. Each concentration was measured three times in parallel using the same sensor. The test results are shown in Table 1 below. The spiked recovery rate was 95.14%–107.16%, and the coefficient of variation (RSD) was 2.93%–5.69%, indicating that the sensor of this invention is suitable for sensitive detection of dinotefuran in complex matrices.
[0068] Table 1. Pesticide detection results of the sensor on brown rice samples
[0069] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An electrochemical sensor based on heteroatom-doped carbon materials, characterized in that, The sensor includes a working electrode, a counter electrode, and a reference electrode. The working electrode includes a porous support substrate and a functional surface layer. The functional surface layer is a continuous porous solid layer that covers and is embedded in the surface pores of the porous support substrate. The functional surface layer is a composite material of heteroatom-doped carbon material and nanocellulose aerogel. The nanocellulose in the nanocellulose aerogel interweaves to form a continuous skeleton structure. After the heteroatom-doped carbon material and nanocellulose hydrogel are mixed, they are subjected to directional freezing and freeze-drying treatment to induce the directional growth of ice crystals, so that the nanocellulose hydrogel forms directionally arranged, interconnected channels, thus forming a composite material of heteroatom-doped carbon material and nanocellulose aerogel. The process of directional freezing and freeze-drying includes: placing the composite sol of heteroatom-doped carbon material and nanocellulose hydrogel at -50 to -80°C for 10 to 30 minutes, and then freeze-drying it at a pressure of 0.005 to 0.05 mbar for 48 to 96 hours; Heteroatom-doped carbon materials are materials formed by mixing carbon precursors and heteroatom dopants and then heat-treating them at high temperatures. The carbon precursors have a porous structure, and the heteroatom dopants are embedded in the carbon lattice of the carbon precursors after heat treatment at high temperatures, forming a heteroatom-carbon doping structure and creating active sites. The carbon precursor is at least one of activated carbon, carbon nanotubes, graphene, graphene oxide, and biomass carbon source; The heteroatom dopant is any one or more boron-containing compounds, sulfur-containing compounds, or phosphorus-containing compounds.
2. The electrochemical sensor based on heteroatom-doped carbon materials according to claim 1, characterized in that, The doped structure formed by heteroatom dopants and carbon precursors after high-temperature heat treatment includes (1) Substitutional doping structure, where heteroatoms replace carbon atoms in the carbon precursor; (2) Defect-type doped structure: after heteroatoms are embedded in carbon precursors, carbon lattice is distorted, edge defects or structural vacancies are formed, thus forming active defect sites.
3. The electrochemical sensor based on heteroatom-doped carbon materials according to claim 1, characterized in that, The surface of heteroatom-doped carbon materials contains oxygen-containing functional groups, and the hydroxyl groups on the surface of nanocellulose form hydrogen bonds with the oxygen-containing functional groups on the surface of heteroatom-doped carbon materials.
4. An electrochemical sensor based on heteroatom-doped carbon materials according to any one of claims 1-3, characterized in that, Electrochemical sensors based on heteroatom-doped carbon materials are used to detect neonicotinoid pesticides.
5. A method for preparing an electrochemical sensor based on heteroatom-doped carbon materials as described in any one of claims 1-4, characterized in that, The preparation steps of the working electrode are as follows: Step S1. Mix the carbon precursor with the heteroatom dopant and perform high-energy ball milling. Then, perform high-temperature heat treatment and purification treatment in an inert gas environment to obtain the heteroatom-doped carbon material. Step S2. Mix and homogenize the heteroatom-doped carbon material obtained in step S1 with nanocellulose hydrogel to obtain a composite sol; Step S3. Load the composite sol from step S2 onto a porous support substrate and perform directional freezing and freeze-drying treatment. The directional freezing and freeze-drying treatment process includes: placing the composite sol of heteroatom-doped carbon material and nanocellulose hydrogel at -50 to -80°C for 10 to 30 minutes, and then freeze-drying it under a pressure of 0.005 to 0.05 mbar for 48 to 96 hours to obtain a composite electrode of heteroatom-doped carbon material and nanocellulose aerogel, which is the working electrode of the sensor.
6. The method for preparing an electrochemical sensor based on heteroatom-doped carbon materials according to claim 5, characterized in that, The high-temperature heat treatment conditions for mixing carbon precursors with heteroatom dopants include: (1) Inert gas environment; (2) The heating rate is 5–20 °C / min; (3) The heat preservation temperature is 500-1500℃, and the heat preservation time is 1-5 hours; After high-temperature heat treatment, it is naturally cooled and then purified.
7. The method for preparing an electrochemical sensor based on heteroatom-doped carbon materials according to claim 5, characterized in that, In heteroatom-doped carbon materials, the mass ratio of carbon precursor to heteroatom dopant is 10:1 to 1:
5.
8. The method for preparing an electrochemical sensor based on heteroatom-doped carbon materials according to claim 5, characterized in that, The ratio between heteroatom-doped carbon material and nanocellulose hydrogel is as follows: 0.01 to 0.5 g of heteroatom-doped carbon material is added to every 10 mL of nanocellulose hydrogel, and the mass fraction of nanocellulose hydrogel is 0.5 to 5 wt%.
Citation Information
Patent Citations
Electrochemical sensor for detecting organophosphorus pesticide and preparation method thereof
CN113390943A
Lithium iron phosphate positive electrode material and preparation method and application thereof
CN118479440A